Taxonomic revision of the Neotropical Augiades Hübner, [1819] (Lepidoptera: Hesperiidae) - Siewert, Ricardo Russo; Lemes, José Ricardo Assmann; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2022)
The Neotropical skipper genus Augiades Hübner, [1819] (Lepidoptera: Hesperiidae) is revised. Neotypes are designated for Hesperia vespasius Fabricius, 1793, and Phareas epimethea Plötz, 1883. Lectotypes are designated for Papilio crinisus Cramer, 1780, and Lignyostola crinisus var. bicolor Mabille & Boullet, 1919. Illustrations of adults and male and female genitalia, distribution maps, and an identification keys are provided for all taxa.